Association of IL1RN VNTR polymorphism with chikungunya infection: A study from Western India. Issue 11 (23rd July 2019) - Tripathy, Anuradha S.; Ganu, Mohini A.; Sonam, Lata; Alagarasu, K.; Walimbe, Atul M.; Thanapati, Subrat; Gupta, Pooja; Puranik, Shaila
Abstract: Chikungunya, caused by the chikungunya virus (CHIKV) mostly presents as acute and chronic articular inflammatory manifestations. Interleukin 1 receptor antagonist (IL‐1RN) is a potent endogenous competitive inhibitor of IL‐1α and 1β and has an anti‐inflammatory role. The present study evaluated the possible association of IL1RN variable number tandem‐repeat (VNTR) alleles and genotypes, and CHIKV stimulated IL‐1RN cytokine production with resistance and/or susceptibility to chikungunya infection and disease state in 224 patients with chikungunya (61 patients with acute chikungunya and 163 patients with chronic chikungunya) and 355 healthy controls. Polymerase chain reaction, CHIKV stimulated cytokine assay and luminex platform were used for assessing polymorphism and protein levels respectively. The study revealed a significant association of IL1RN *1/*1 genotype under recessive genetic model with the risk of developing chikungunya infection. Our findings also indicated that IL1RN *2 allele under dominant mode was associated with protection to chronic chikungunya. The results also revealed a higher production of IL‐1 RN protein in patients with chronic chikungunya. To conclude, the results suggest the association of ILRN VNTR polymorphism and IL‐RN protein levels with chronic chikungunya.